2007
DOI: 10.1007/s10735-007-9099-0
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Cajal-like cells in human gallbladder

Abstract: We describe here an interstitial Cajal-like cell type (ICLC) in human gallbladder, resembling the archetypal enteric interstitial cells of Cajal. Gallbladder ICLC were demonstrated in fresh preparations (tissue cryosections) using methylene-blue, and fixed specimens in Epon semi-thin sections stained with toluidine blue or transmission electron microscopy (TEM). The positive diagnosis of gallbladder ICLC was further verified by immunohistochemistry: CD117/c-kit, CD34, and another 16 antigens: vimentin, desmin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
74
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 69 publications
(78 reference statements)
4
74
0
3
Order By: Relevance
“…Cells with the morphological features of ICC have also been reported recently in the murine (43) and human (13) sparks, play a fundamental role in GBSM rhythmic activity (2,27,34). These findings correspond with observations in GI tract (49,50) and suggest that intracellular Ca 2ϩ mobilization, involving both SR and mitochondria, may be essential for the generation and propagation of rhythmic electrical activity in the gallbladder as has been observed in the GI tract (15, 38, 48 -52) and the urinary bladder (19).…”
mentioning
confidence: 72%
“…Cells with the morphological features of ICC have also been reported recently in the murine (43) and human (13) sparks, play a fundamental role in GBSM rhythmic activity (2,27,34). These findings correspond with observations in GI tract (49,50) and suggest that intracellular Ca 2ϩ mobilization, involving both SR and mitochondria, may be essential for the generation and propagation of rhythmic electrical activity in the gallbladder as has been observed in the GI tract (15, 38, 48 -52) and the urinary bladder (19).…”
mentioning
confidence: 72%
“…Interstitial Cajal-like cells (ICLCs) are known to play a pivotal role in controlling gastrointestinal tract motility by providing electrical impulses for slow wave generation and by regulating smooth muscle activity and neurotransmission [25]. ICLCs were observed throughout the gallbladder, although they were mostly located in the body [26]. The incision made on the fundus of the gallbladder to minimize damage to ICLCs and reduce the effect the recovery of gallbladder motility.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, complete removal of ICC from tissue fragments depresses a lot contraction reaction of myocytes to CCK-8 [9]. Moreover, studies revealed that damage to interstitial Cajal-like cells (ICLCs) in the gallbladder wall of patients with cholelithiasis could be related to an increased bile lithogenicity index or chronic inflammatory processes involving a gallbladder filled with gallstones [17]. Both mechanisms may participate in gallstone formation by reducing the number of ICLCs in the gallbladder wall.…”
Section: Role Of Iccmentioning
confidence: 99%